Taking stock of global land indicators: A comparative analysis of approaches for a globally consistent land tenure security measure. (January 2023) - Huntington, Heather; Stevens, Caleb
Abstract: Land is important and underpins many of the Sustainable Development Goals (SDGs). The need for reporting on SDGs has elicited a boom in efforts to measure land tenure security. As land tenure security has not been the subject of systematic data collection in the past, efforts are underway to develop and implement a globally consistent approach to measuring land tenure security. This paper investigates two approaches - Prindex and the SDG joint land module - that have recently been put forward as consistent and reliable measures for capturing the data needed to advance our understanding of land tenure security. The paper describes the differences between the approaches in terms of sampling, methodology, and questionnaire wording, and highlights their strengths and weaknesses across four dimensions: consistency, cost-effectiveness, sustainability, and accessibility. This study finds that, under many circumstances, the Prindex and SDG approaches will produce different empirical results and policy recommendations. The difference in results does not indicate that one method is better or worse than the other, however, caution should be taken in treating these sources as substitutes. Overall, they are complementary approaches to inform on-going and future policy and programming efforts. Highlights: Comparative analysis of approaches to measuring tenure security. Strengths and weaknesses of Prindex and SDG joint land module as global indicators. Global tenure security indicators as compliments versus substitutes. Different global indicators produce different empirical results.